Development of Industrial and Agricultural Enterprises on the Basis of Innovation Management - CHOMANOV, Urishbay Ch.; TULTABAEVA, Tamara Ch.; KENENBAY, Gulmira S.; TULTABAEV, Mukhtar Ch.; SHOMAN, Erbokyzy A. (Journal of Advanced Research in Law and Economics, 2019)
The development of industry by innovative type in order to increase the competitive advantages of industrial enterprises, requires a radical update of innovation management mechanisms, improvement of methods and management tools in innovation, since the overall situation in the domestic industry is characterized by a practical lack of effective, mobile, and, ultimately, competitive economic entities susceptible to technological and organizational innovations. Currently, the development of the industrial complex of Russia is characterized by the imbalance of the elements of innovation, low competitiveness of finished products and low level of implementation of advanced scientific developments. Very significant are the entry barriers to innovation in industrial production, due to the lack of motivation of economic entities to choose a model of innovative development. This has a negative impact on the competitiveness of products, does not contribute to the strengthening of the position of domestic industries in the global market. In order to ensure better growth of industries and change the current situation, it is necessary to carry out a fundamental transformation of the mechanisms of innovative development and ensure effective management of innovative activities of industrial enterprises. The recipes of the protein complex with the addition of vegetable raw materials have been developed. Experimental studies were conducted to determine the amount of plant additives based on the organoleptic characteristics of the product.